Neotypification of Delphinium dasycaulon (Ranunculaceae) - Jabbour, Florian; Dressler, Stefan (Phytotaxa, 2015)
The afromontane species Delphinium dasycaulon Fresenius (1837: 272) is one of the three species of Delphinium Linnaeus (1753: 530) (Ranunculaceae) distributed in tropical Africa. This perennial plant has a disjunct distribution, with isolated populations in East Africa (from Djibouti and Eritrea in the North to Malawi and Zambia in the South) and West Africa (Cameroon and Nigeria) (Milne-Redhead & Turrill 1952). Interestingly, no specimen has ever been collected in the central part of the East African Rift region (Kenya and Uganda), where the two other afromontane species of the genus occur: D. macrocentrum Oliver (1886: 397) which is endemic on Mt. Elgon and in the Kenyan Highlands, and D. leroyi Franchet ex Huth (1895: 474), which has a broader distribution in tropical East Africa ranging from Ethiopia in the North to Tanzania in the South (Milne-Redhead & Turrill 1952).